The knowledge exchange and dissemination plan of the We Can Quit2 community-based stop-smoking trial. (20th October 2021) - Castello, S; Darker, C; Vance, J; Buckley, E; Reynolds, C; Cronin, N; Dougall, N; Devane, D; Bauld, L; Hayes, CB
Abstract: Background: We Can Quit2 was a community-based randomised controlled trial which determined the feasibility and acceptability of We Can Quit (WCQ), a peer delivered stop-smoking programme comprising group support and free Nicotine Replacement Therapy (NRT) tailored to women living in socioeconomically disadvantaged areas in Ireland. Reengagement with key stakeholders took place as part of the trial Knowledge Exchange and Dissemination plan, to discuss strategies to optimise community engagement, recruitment and retention in a future definitive trial (DT), and the policy priorities arising from the trial. Methods: Community stakeholders involved in trial recruitment and planning, Irish Cancer Society and Health Service Executive representatives were invited to an online interactive workshop in November 2020. Key trial findings were presented. Workshop discussion (field notes) and responses to a post-event anonymous questionnaire informed a list of challenges and suggestions for a future DT and policy development from a community perspective. Results: Forty-one stakeholders attended the workshop, six completed the questionnaire. Dedicated additional time for community engagement and use of social prescribing as a recruitment tool were recommended. Greater adaptation of trial data and assistance to complete forms were suggested to address low literacy, which was a barrier to recruitment and retention. An intervention boost after WCQ delivery and encouragement of women to join other healthy community programmes to maintain their group, were recommended to facilitate retention and enhance sustainability. Policy priorities were to remove cost and administrative barriers to access NRT and ongoing provision of cessation services tailored to disadvantaged groups. Conclusions: Important strategies to optimise design of a DT of WCQ effectiveness were recommended. Lessons learned may be relevant to other community-based health interventions in socioeconomically disadvantaged areas. Key messages: The workshop provided a suitable forum for engagement of community and statutory stakeholders. Knowledge exchange activities facilitated an enhanced research design from a community perspective.